Infrared Multiphoton Dissociation Spectroscopy with Free-Electron Lasers: On the Road from Small Molecules to Biomolecules - Jašíková, Lucie; Roithová, Jana (Chemistry (Weinheim an der Bergstrasse, Germany), 2018)
Infrared multiphoton dissociation (IRMPD) spectroscopy is commonly used to determine the structure of isolated, mass-selected ions in the gas phase. This method has been widely used since it became available at free-electron laser (FEL) user facilities. Thus, in this Minireview, we examine the use of IRMPD/FEL spectroscopy for investigating ions derived from small molecules, metal complexes, organometallic compounds and biorelevant ions. Furthermore, we outline new applications of IRMPD spectroscopy to study biomolecules.
Keywords: Electrons; Lasers; elektrony; organokovové sloučeniny; Spectrophotometry, Infrared; spektrofotometrie infračervená; IRMPD spectroscopy; solvation; ionty; biomolecules; Organometallic Compounds; lasery; gas phase; Ions; metal complexes